Providing therapeutic services to methamphetamine users and children who have experienced intimate partner violence during the COVID-19 - Azizul, Muhd. Dhamir Audi; Wan Jaafar, Wan Munira; Mohd Khir, Azlina; Amin, Samir Muhazzab (Human Resource Management Academic Research Society, 2022)
World widely, methamphetamine abuse has been associated to intimate partner violence (IPV) and aggression. IPV during COVID-19 became a “pandemic within a pandemic” due to the pressures of economic insecurity, unemployment, and others. However, due to the pandemic, several therapeutic services for children and their parents who had experienced intimate partner violence (IPV) were required to rapidly transition to telehealth. The present study aims to investigate parents' experiences of participating in a parent-child telehealth intervention during the COVID-19 pandemic. In addition, researcher interested to explore counsellors' experiences of delivering the telehealth service. Participants were six fathers who took part in therapeutic service programme in National Anti-Drugs Agency (PUSPEN Melaka, Malaysia and four counsellors who delivered the service in specific regional areas. Semi-structured qualitative interviews were conducted and data were analysed using thematic analysis to determine key themes and sub-themes within the data. Parents acknowledged several benefits of therapeutic services delivered via telehealth including increased client credibility of rehabilitation centre delivered therapeutic service, improved emotion management, and improved paternal relationship. Counsellors acknowledged the significant of telehealth within this context including improved accessibility to the service and therapeutic skills. However, challenges to the telehealth approaches were also noted from parents and counsellors. Physical health problem, technology and child-attention barrier are the key challenge from the parents meanwhile counsellors acknowledge considerations for telehealth within this context including creativity of delivery services and physical health problem. The initial rapid transition to telehealth was described as an acceptable of mod delivery and improved accessibility to the IPV skills in the therapeutic services. Consideration should be looking into challenges of the telehealth and emphasizes the need for severe evaluations of telehealth services for children exposed to IPV.